Influence of Number Location on the SNARC Effect: Evidence From the Processing of Rotated Traditional Chinese Numerical Words. (April 2020) - Wang, Zhiwei; Zhu, Xiaotong; Jiang, Yingjie
Studies have widely captured the spatial-numerical association of response codes (SNARC) effect in the processing of various types of numbers in which small numbers are responded to faster with the left hand than with the right hand and larger numbers are responded to faster with the right hand than with the left hand. Although a few studies have explored Arabic numbers to further investigate the influence of number location on the SNARC effect, it remains unclear whether the influence of number location on the SNARC effect is moderated by numerical semantic processing difficulty and the task performed. This study explored traditional Chinese numerical words and rotated them to certain angles, which can increase numerical semantic processing difficulty, to further investigate the influence of the stimulus–response compatibility effect and Simon effect on the SNARC effect in a space classification task (Experiment 1), numerical magnitude classification task (Experiment 2), numerical parity classification task (Experiment 3), and color classification task (Experiment 4). The results indicated that (a) the stimulus–response compatibility effect, not the SNARC effect, prevailed in the numerical space classification task; (b) the SNARC effect, not the Simon effect, prevailed in the numerical magnitude and parity classification task; and (c) the Simon effect and the SNARC effect coexisted in the color classification task. These results suggested that the influence of number location on the SNARC effect was moderated by the task performed. Implications for the theory of the SNARC effect and Simon effect are discussed.